Enhancing the feasibility of Pd/C-catalyzed formic acid decomposition for hydrogen generation - catalyst pretreatment, deactivation, and regeneration - Kosider, Axel; Blaumeiser, Dominik; Schötz, Simon; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter; Libuda, Jörg; Bauer, Tanja (Catalysis: Science and Technology, 2021)
Formic acid decomposition (FAD) generates H-2 at low temperatures. However, many known catalyst systems suffer from deactivation due to competing side reactions during FAD. In this work, we focus on the origins of the deactivation of Pd catalysts but also on protocols which allow for reactivation of this precious metal catalyst. We combined batch experiments with results from in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We find that CO adsorbates block catalytic sites and deactivate the Pd catalyst. Oxidative treatment lifts this inhibition. Additionally, our results show that oxidative pretreatment activates the Pd catalyst, whereas reduction leads to a catalyst which is essentially inactive for FAD.
CRIS-Team WoS Importer:2021-05-28